Pengaruh Tax Avoidance, Risiko Pajak, dan Ukuran Perusahaan Terhadap Cost of Debt - Alverina Hardianti; Ita Darsita (CV. ITTC INDONESIA, 2025)
This study aims to analyze the effect of tax avoidance, tax risk, and company size on the cost of debt in Infrastructure Sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2023. The sampling technique used in this study uses purposive sampling technique, with quantitative research type. The data used is secondary data, namely the company's annual financial statements. The number of samples used in this study were 12 infrastructure sector companies with observations for 5 (five) years, so that 60 observation objects were selected. The analysis method uses multiple analysis, F test, T test using Eviews software version 12. The results of this study indicate that simultaneously tax avoidance, tax risk, and company size affect the cost of debt. Tax avoidance and tax risk partially did not have any effect on the cost of debt. Meanwhile, company size partially affected the cost of debt.